Development of Tor Tor Dance in Batak Wedding Ceremony in Medan City - Rana Salsabila; Lita Octaviani; Fia Adilla; Hassan Sazali; Maulana Adinata Dalimunthe (Penerbit Jurnal Indonesia, 2022)
Tortor dance for the Batak tribe is used to express feelings in any situation, one of which includes wedding ceremonial activities. Tortor dance is an important part of the Batak indigenous community, which has cultural values and spiritual values. Through the Batak indigenous Tortor dance in Medan, it conveys its hopes and prayers. The movement or demonstration of attitudes and feelings through this Tortor dance adorn the situation and conditions that are being experienced. The purpose of this study is to determine the development of Tortor dance in a brick wedding ceremony in Medan. This study uses a case study method with a qualitative approach. The data collected is primary data obtained from several speakers. From the result of research in the field that the Tortor dance in Batak wedding ceremony in Medan shows that every hand movement has meaning and significance